Placental pathology in a pregnant woman with severe COVID-19 and successful ECMO treatment: a case report - Anna Rosner-Tenerowicz; Tomasz Fuchs; Aleksandra Zimmer-Stelmach; Michał Pomorski; Martyna Trzeszcz; Jacek Zwierzchowski; Mariusz Zimmer (BMC, 2021)
Abstract Background Infection with SARS-CoV-2 during pregnancy can lead to a severe condition in the patient, which is challenging for obstetricians and anaesthesiologists. Upon severe COVID-19 and a lack of improvement after multidrug therapy and mechanical ventilation, extracorporeal membrane oxygenation (ECMO) is introduced as the last option. Such treatment is critical in women with very preterm pregnancy when each additional day of the intrauterine stay is vital for the survival of the newborn. Case presentation We report a case of a 38-year-old woman at 27 weeks of gestation treated with multidrug therapy and ECMO. The woman was admitted to the intensive care unit (ICU) with increasing fever, cough and dyspnoea. The course of the pregnancy was uncomplicated. She was otherwise healthy. At admission, she presented with severe dyspnoea, with oxygen saturation (SpO2) of 95% on passive oxygenation, heart rate of 145/min, and blood pressure of 145/90. After confirmation of SARS-CoV-2 infection, she received steroids, remdesivir and convalescent plasma therapy. The foetus was in good condition. No signs of an intrauterine infection were visible. Due to tachypnea of 40/min and SpO2 of 90%, the woman was intubated and mechanically ventilated. Due to circulatory failure, the prothrombotic activity of the coagulation system, further saturation worsening, and poor control of sedation, she was qualified for veno-venous ECMO. An elective caesarean section was performed at 29 weeks on ECMO treatment in the ICU. A preterm female newborn was delivered with an Apgar score of 7 and a birth weight of 1440 g. The newborn had no laboratory or clinical evidence of COVID-19. The placenta showed the following pathological changes: large subchorionic haematoma, maternal vascular malperfusion, marginal cord insertion, and chorangioma. Conclusions This case presents the successful use of ECMO in a pregnant woman with acute respiratory distress syndrome in the course of severe COVID-19. Further research is required to explain the aetiology of placental disorders (e.g., maternal vascular malperfusion lesions or thrombotic influence of COVID-19). ECMO treatment in pregnant women remains challenging; thus, it should be used with caution. Long-term assessment may help to evaluate the safety of the ECMO procedure in pregnant women.